Overview of the Australian Institute of Sport European Training Centre - Forbes, W. (Elite Training Seminar Series, 2018)
The Australian Institute of Sport European Training Centre in Varese, Italy is used by a wide range of sports and, when not being used by Australian Teams, is open to visiting teams from around the world.